Long-term Resolution of Immunological Graft Rejection After a Dexamethasone Intravitreal Implant. Issue 4 (April 2015) - Vinciguerra, Paolo; Albé, Elena; Vinciguerra, Riccardo; Romano, Mario M.; Trazza, Silvia; Mastropasqua, Leonardo; Epstein, Daniel
Abstract : Purpose: To present the results of the injection of an intravitreal implant of dexamethasone 0.7 mg (DEX 0.7 mg) in 4 patients with an immunologic graft rejection after penetrating keratoplasty. Methods: Two of the patients received DEX 0.7 mg because inflammation and corneal edema not related to endothelial cell loss persisted despite the administration of topical prednisolone acetate, subconjunctival betamethasone, and systemic methylprednisolone. The other 2 cases received DEX 0.7 mg at the time rejection was diagnosed. Results: At 1 and 6 months after implantation, all rejection episodes resolved with improvement in uncorrected and best-corrected visual acuity, restoration of graft transparency, reduction of central corneal thickness, and no significant increase in intraocular pressure. Conclusions: In 4 eyes with an immunologic graft rejection after penetrating keratoplasty, the dexamethasone 0.7 mg intravitreal implant was an effective treatment option, even in cases refractory to standard topical and systemic therapy.